Longitudinal prediction of periconception alcohol use: a 20‐year prospective cohort study across adolescence, young adulthood and pregnancy. (8th September 2021) - Hutchinson, Delyse; Spry, Elizabeth A.; Mohamad Husin, Hanafi; Middleton, Melissa; Hearps, Stephen; Moreno‐Betancur, Margarita; Elliott, Elizabeth J.; Ryan, Joanne; Olsson, Craig A.; Patton, George C.
Abstract: Background and Aims: Alcohol consumption is common in adolescence and young adulthood and may continue into pregnancy, posing serious risk to early fetal development. We examine the frequency of periconception alcohol use (prior to pregnancy awareness) and the extent to which adolescent and young adult alcohol use prospectively predict periconception use. Design: A longitudinal, population‐based study. Setting: Victoria, Australia. Participants: A total of 289 women in trimester three of pregnancy (age 29–35 years; 388 pregnancies). Measures: The main exposures were binge [≥ 4.0 standard drinks (SDs)/day] and frequent (≥ 3 days/week) drinking in adolescence (mean age = 14.9–17.4 years) and young adulthood (mean age 20.7–29.1 years). Outcomes were frequency (≥ 3 days/week, ≥ monthly, never) and quantity (≥ 4.0 SDs, ≥ 0.5 and < 4.0 SDs, none) of periconception drinking. Findings: Alcohol use was common in young adulthood prior to pregnancy (72%) and in the early weeks of pregnancy (76%). The proportions drinking on most days and binge drinking were similar at both points. Reflecting a high degree of continuity in alcohol use behaviours, most women who drank periconceptionally had an earlier history of frequent (77%) and/or binge (85%) drinking throughout the adolescent or young adult years. Young adult binge drinking prospectively predicted periconception drinking quantity [odds ratio (OR) = 3.7, 95% confidence interval (CI) = 1.9–7.4], compared with women with no prior history. Similarly, frequent young adult drinking prospectively predicted frequent periconception drinking (OR = 30.7, 95% CI = 12.3–76.7). Conclusions: Women who engage in risky (i.e. frequent and binge) drinking in their adolescent and young adult years are more likely to report risky drinking in early pregnancy prior to pregnancy recognition than women with no prior history of risky drinking.